Activity Cost Management and its Effect on Enterprise Productivity - Ugoani, John Nkeobuna Nnah (International Journal of Business, Economics and Management, 2019)
This study investigated the relationship between activity cost management and its effect on enterprise productivity using the exploratory research design. It focused on critical factors that lead to cost-effectiveness. A sample of 113 respondents participated in the study, and data collected from secondary and primary sources were analyzed through descriptive and regression statistical techniques. The result showed that activity cost management has significant positive effect on enterprise productivity. The new result is important because an enterprise is effective when it attains its goals, but productive only when such goals are achieved efficiently. Through the exploration and result, the study clearly highlighted that factors such as activity-based cost management, cost-benefit-analysis, internal control, ratio analysis, zero-base budgeting, internal accountability, and transparency, as well as cost leadership form the basis for enterprise productivity. An effective board of directors is imperative in any enterprise to provide necessary cost leadership for cost-effectiveness and enterprise productivity. The study was limited by insufficient current academic literature, therefore, further study could examine the relationship between activity cost management and enterprise failure. Based on the result, it was recommended that activity cost management practices must be intensified in public enterprises as a measure to reduce the heap of fraud prevalent in such enterprises.